The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s12883-017-0807-4
|View full text |Cite
|
Sign up to set email alerts
|

Kikuchi-Fujimoto disease (histiocytic necrotizing lymphadenitis) with atypical encephalitis and painful testitis: a case report

Abstract: BackgroundKikuchi-Fujimoto disease is a self-limited clinicopathologic entity that is increasingly recognized worldwide. Kikuchi-Fujimoto disease is characterized by cervical lymphadenopathy occurring in young adults. Neurologic involvement is rare, and testitis directly caused by Kikuchi-Fujimoto disease has not yet been reported.Case presentationA 19-year-old man was brought to our clinic with complaints of fever, headache, fatigue, and left lower quadrant pain that had persisted for 3 weeks. On physical exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Given the recent diagnosis via cervical node biopsy, knowledge that KFD can lead to CNS involvement, improvement in the lesion without treatment, and rapid resolution, the lesion is a presumed complication of Kikuchi-Fujimoto disease. 5 The unique aspect of this single case is the resolution with supportive management because she did not receive steroids or immunomodulating therapy since the onset of her weakness. This suggests that, in some cases, the CNS lesions of KFD may resolve with supportive care.…”
Section: Discussionmentioning
confidence: 95%
“…Given the recent diagnosis via cervical node biopsy, knowledge that KFD can lead to CNS involvement, improvement in the lesion without treatment, and rapid resolution, the lesion is a presumed complication of Kikuchi-Fujimoto disease. 5 The unique aspect of this single case is the resolution with supportive management because she did not receive steroids or immunomodulating therapy since the onset of her weakness. This suggests that, in some cases, the CNS lesions of KFD may resolve with supportive care.…”
Section: Discussionmentioning
confidence: 95%
“…Third, we encountered an unusual case of encephalitis associated with Kikuchi disease. There are few cases of encephalitis accompanied by Kikuchi disease (5)(6)(7)(8)(9). Byun et al reported the clinical and MRI findings of nine patients with encephalitis associated with Kikuchi disease (9).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations of KFD involving the CNS are complex and diverse, including meningitis, encephalitis, subdural effusion, optic neuritis, cerebellar ataxia, hemiplegia, and other signs (10,23,(34)(35)(36)(37)(38). KFD concomitant with neurological symptoms is rare and prone to missed diagnosis and misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%